Pengembangan Soft Skill Peserta Didik melalui Perpustakaan Berbasis Inklusi Sosial (Studi di Madrasah Tsanawiyah Negeri 3 Jombang) - Nurul Swandari; Abdurahman Jemani (Lembaga Bale Literasi, 2023)
An inclusive school library encourages active and collaborative participation. This means encouraging the involvement of all students in library activities. Therefore, this study aims to explore the potential for developing students' soft skills through a library that focuses on social inclusion. Through this research, it is hoped that practical strategies and approaches can be found that can be applied in school library management to improve students' soft skills effectively. This study uses a qualitative approach with a single case study design. The participants in this study were 860 grade 7 students at Madrasah Tsanawiyah Negeri 3 Jombang in the odd semester of 2022/2023 and were grouped into 7 soft skill development trial groups. The results achieved in this study were success in honing seven types of soft skills (communication skills, collaboration skills, creativity and innovation, leadership, digital skills, time management skills, and problem solving skills) through various activities.